Internal topology and water transport in tetrafunctional epoxy resins. Issue 30 (30th May 2022) - Morsch, Suzanne; Lyon, Stuart B.; Gibbon, Simon; Irwin, Mark
Abstract: Water sorption into epoxy resins limits the performance lifetime of many composites, adhesives, and coatings. One hypothesis for the well‐known hygroscopicity of epoxies is that the well‐known internal nodular topology of epoxy networks enhances permeability. This theory has however remained untested to date, since previous attempts to manipulate the internal topology have been accompanied by changes in the hydrogen bonding capability of resins, which dominates water uptake. Here, the nanostructure of highly cross‐linked network polymers based on tetra glycidyl diaminodiphenyl methane is varied in the absence of significant polarity effects by careful optimization of the cure schedule. The internal morphology of resins cured at 100, 150, and 200°C are characterized using Peakforce tapping mode atomic force microscopy, whilst the cure progression at each temperature is analyzed using in‐situ transmission mode infrared spectroscopy. Distinct nodular morphologies are found to form at high cure temperatures (150 and 200°C), where spectroscopic analysis demonstrates that excess epoxy consumption occurs prior to the gel point, as a result of intra‐cluster cross‐linking and reduced reaction selectivity. Surprisingly, the establishment of an internal nanostructure is, however, found to have negligible effect on the extent and kinetics of moisture sorption. Abstract : The internal topology of an epoxy‐phenolic resin is controlled using only the cure schedule, and its effect on moisture uptake is investigated using dynamic vapor sorption. Absorption isotherms shows that the presence of heterogeneously cross‐linked nanostructures has no effect on the overall extent, or kinetics, of water sorption. In contrast, minimal surface oxidation results in significantly increased moisture content.